A slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete and its preparation method

CN122789653APending Publication Date: 2026-09-22FENGCHENG NEW CITY INVESTMENT & CONSTRUCTION GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611028070.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

现有研究中虽有采用硅烷偶联剂或聚合物乳液对骨料进行预处理的报道,但上述方法普遍存在处理工序复杂、与减水剂体系相容性差等问题,尚无成熟的一体化解决方案

Benefits of technology

(1)本发明提供的用于再生骨料混凝土的保坍减缩型聚羧酸减水剂,采用三组分复配体系,通过缓释型聚羧酸减水剂、改性剂与聚丙二醇类减缩助剂的协同作用,针对再生骨料混凝土吸水率高、孔隙结构复杂、坍落度损失快、干燥收缩大等问题提供综合解决方案,在单一产品中实现了保坍与减缩功能的有机统一,避免了多组分外加剂叠加使用时的相容性风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1783672555033-000001
    Figure REF-OBJ-1783672555033-000001
Patent Text Reader

Abstract

This invention discloses a slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete and its preparation method. By weight, it comprises the following raw materials: 70-80 parts of slow-release polycarboxylate superplasticizer, 15-25 parts of modifier, and 5-10 parts of polypropylene glycol shrinkage-reducing additive. This slump-retaining and shrinkage-reducing polycarboxylate superplasticizer uses a three-component compound system. Through the synergistic effect of the slow-release polycarboxylate superplasticizer, modifier, and polypropylene glycol shrinkage-reducing additive, it provides a comprehensive solution to problems such as high water absorption, complex pore structure, rapid slump loss, and large drying shrinkage in recycled aggregate concrete. It achieves an organic unity of slump retention and shrinkage reduction functions in a single product, avoiding the compatibility risks associated with the combined use of multiple admixtures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water-reducing agent technology, specifically relating to a slump-retaining and shrinkage-reducing polycarboxylate water-reducing agent for recycled aggregate concrete and its preparation method. Background Technology

[0002] Recycled aggregate concrete (RAC) is concrete made by partially or completely replacing natural aggregates with recycled aggregates obtained from the crushing and screening of construction demolition waste. With the advancement of policies promoting the resource utilization of solid waste in the construction industry, the application of recycled aggregate concrete in engineering projects is becoming increasingly widespread. However, compared with natural aggregates, recycled aggregates have a large amount of residual cement mortar adhering to their surface and micro-cracks inside, resulting in high water absorption (typically 3-8 times that of natural aggregates), rough surfaces, and high porosity. These characteristics significantly impair the workability and volume stability of recycled aggregate concrete, restricting its engineering application.

[0003] In terms of workability, the high water absorption of recycled aggregates leads to a rapid decrease in the free water content of concrete mixtures over time, significantly exacerbating slump loss. Polycarboxylate superplasticizers (PCEs), as the most widely used high-performance superplasticizers, have had their water-reducing and dispersing effects well-proven. However, conventional PCEs are easily adsorbed in large quantities by the pores of recycled aggregates in recycled aggregate concrete systems, causing the effective concentration of the superplasticizer to drop rapidly in a short period, resulting in significant slump loss over time. Existing research on slump retention mainly focuses on improving the situation by optimizing the molecular structure of PCE (such as adjusting side chain density and introducing slow-release groups) or using pre-saturated aggregates, but the effects are limited, and the pre-saturation process is cumbersome and difficult to promote in engineering projects.

[0004] In terms of volume stability, recycled aggregate concrete, due to pre-existing microcracks within the aggregate, interfacial transition zone (ITZ) defects, and higher porosity, typically exhibits greater shrinkage deformation (including drying shrinkage and autogenous shrinkage) than ordinary concrete, making it more prone to cracking. One of the main driving forces behind concrete shrinkage is the capillary negative pressure generated by water evaporation in the capillaries. Reducing the surface tension of the pore solution or decreasing the driving force of capillary shrinkage is an effective way to control shrinkage. Existing shrinkage-reducing agents mostly use small-molecule alcohol ether compounds, which, while having a certain shrinkage-reducing effect, can affect the cement hydration process and concrete strength development to varying degrees. Furthermore, in practical engineering, using shrinkage-reducing agents alone is difficult to simultaneously address the slump loss problem.

[0005] Furthermore, the porous structure of residual cement mortar on the surface of recycled aggregates allows admixtures to enter the aggregate interior in large quantities through physical adsorption and capillary absorption, further exacerbating the ineffective consumption of water-reducing agents. How to effectively seal the surface pores of recycled aggregates to reduce water-reducing agent loss without significantly increasing process complexity is one of the current challenges in the research of recycled aggregate concrete admixtures. While existing research has reported the use of silane coupling agents or polymer emulsions for aggregate pretreatment, these methods generally suffer from complex processing procedures and poor compatibility with water-reducing agent systems, and a mature integrated solution is still lacking.

[0006] Therefore, developing a composite polycarboxylate superplasticizer system that can simultaneously solve the problems of large slump loss, high shrinkage deformation, and low effective utilization rate of water-reducing agents in recycled aggregate concrete has significant engineering value and practical significance. Summary of the Invention

[0007] To address the shortcomings of existing technologies, the present invention aims to provide a slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete and its preparation method.

[0008] To achieve the above objectives, the present invention provides the following technical solution: A slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete, comprising the following raw materials by weight: 70-80 parts of slow-release polycarboxylate superplasticizer, 15-25 parts of modifier, and 5-10 parts of polypropylene glycol shrinkage reducing agent.

[0009] Preferably, a slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete comprises, by weight, the following raw materials: 75-80 parts of slow-release polycarboxylate superplasticizer, 20-25 parts of modifier, and 7-10 parts of polypropylene glycol shrinkage-reducing additive.

[0010] Preferably, the preparation method of the slow-release polycarboxylate superplasticizer is as follows: Add ethylene glycol monovinyl polyethylene glycol ether, acrylic acid, hydroxyethyl acrylate and 2-(phosphoryloxy)ethyl acrylate to deionized water, stir until homogeneous to obtain a mixed solution, add ammonium persulfate aqueous solution and vitamin C aqueous solution dropwise, carry out a constant temperature reaction, add NaOH solution after the reaction is completed, adjust the pH, filter, and finally add water to the preset solid content to obtain the final product.

[0011] Preferably, the molecular weight of the ethylene glycol monovinyl polyethylene glycol ether is 2000-3000 Da; the mass ratio of the deionized water, ethylene glycol monovinyl polyethylene glycol ether, acrylic acid, hydroxyethyl acrylate, and 2-(phosphoryloxy)ethyl acrylate is 100:120-180:8-14:4-10:3-8; the mass fraction of the ammonium persulfate aqueous solution is 5-8%, and the amount used is 8-12% of the mass of the mixed solution; the mass fraction of the vitamin C aqueous solution is 1-3%, and the amount used is 5-8% of the mass of the mixed solution; the isothermal reaction temperature is 20-30℃, and the time is 1-2 hours; the pH is 6-7; and the preset solid content is 40-50%.

[0012] Preferably, the method for preparing the modifier includes the following steps: S1. Disperse chitosan powder in deionized water, adjust the pH to 10-11, add 3-chloro-2-hydroxypropyltrimethylammonium chloride, stir and react, dialyze to purify after the reaction is complete, freeze dry to obtain quaternized chitosan; S2. Add gluconic acid to MES buffer, add EDC and NHS for activation to obtain activated gluconic acid solution; add quaternized chitosan to deionized water, stir and adjust pH to 7-7.5, then add gluconic acid solution dropwise, carry out constant temperature reaction, after the reaction is completed, dialysis purification, freeze drying to obtain gluconic acid modified chitosan. S3. Polyethylene glycol monomethyl ether was reacted with succinic anhydride in anhydrous pyridine and purified to obtain carboxylated polyethylene glycol. Then, it was added to PBS buffer, and EDC and NHS were added for activation to obtain an activated solution. Gluconic acid-modified chitosan was added to PBS buffer, followed by the addition of the activated solution to carry out an amidation reaction. After the reaction was completed, it was purified by dialysis and freeze-dried to obtain the modifier.

[0013] Preferably, in step S1, the mass ratio of chitosan, deionized water, and 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1:20-30:0.6-0.8, and the stirring reaction temperature is 55-65℃ for 5-7 hours.

[0014] In this invention, 3-chloro-2-hydroxypropyltrimethylammonium chloride is used to quaternize chitosan, introducing quaternary ammonium groups with permanent positive charges. Alkaline conditions are conducive to the deprotonation of the amino groups of chitosan, improving its nucleophilic reactivity, thereby enabling it to undergo a highly efficient nucleophilic substitution reaction with the quaternizing agent. The resulting quaternized chitosan carries a positive charge over a wide pH range, providing a stable cationic framework for subsequent steps and endowing the modifier with the ability to electrostatically adsorb onto the negatively charged surface of recycled aggregate.

[0015] Preferably, in step S2, the mass ratio of gluconic acid, MES buffer, EDC, and NHS is 1:15-25:0.8-1.2:0.5-0.8, the activation temperature is 20-25℃, and the time is 40-50 min; the mass ratio of quaternized chitosan, deionized water, and gluconic acid solution is 1:20-40:8-12, the isothermal reaction temperature is 20-25℃, and the time is 12-16 h; the molecular weight cutoff for dialysis is 3500 Da, the dialysis time is 48 h, and the water is changed every 12 h.

[0016] In this invention, gluconic acid is grafted onto quaternized chitosan using an EDC / NHS chemical coupling method. Glucolic acid carries multiple hydroxyl groups, and after grafting, a large number of hydrophilic hydroxyl groups can be introduced into the quaternized chitosan backbone. On the one hand, this enhances the hydrogen bonding ability between the modifier and the inner wall of the recycled aggregate pores, which helps the modifier to be stably enriched at the pore openings; on the other hand, it improves the overall water solubility and dispersion stability of the modifier, which is beneficial to its uniform distribution in the concrete system. During the activation stage, MES buffer (pH 5.5-6.0) is used to maintain the optimal reaction environment of EDC / NHS, and during the grafting reaction stage, the pH is adjusted to 7-7.5 to promote the efficient formation of amide bonds.

[0017] Preferably, in step S3, the molecular weight of the polyethylene glycol monomethyl ether is 400-1000 Da, the mass ratio of the polyethylene glycol monomethyl ether to succinic anhydride is 1:0.15-0.25, the reaction temperature is 45-55℃, and the time is 8-12 h; the mass ratio of the carboxylated polyethylene glycol, PBS buffer, EDC, and NHS is 1:10-20:0.4-0.6:0.25-0.4, the activation temperature is 20-25℃, and the time is 40-50 min; the mass ratio of the gluconate-modified chitosan, PBS buffer, and activation solution is 1:20-30:5-9, the amidation reaction temperature is 20-25℃, and the time is 18-24 h; the molecular weight cutoff for dialysis is 10000 Da, and the dialysis time is 72 h.

[0018] In this invention, polyethylene glycol monomethyl ether (mPEG) is first reacted with succinic anhydride in anhydrous pyridine to introduce carboxyl groups at the terminal hydroxyl groups, resulting in carboxylated polyethylene glycol. After activation by EDC / NHS, it undergoes an amidation reaction with the residual amino groups of gluconic acid-modified chitosan, grafting PEG segments onto the chitosan backbone. The introduction of PEG segments endows the modifier with good steric hindrance and lubrication effects, effectively reducing slurry viscosity and producing a synergistic dispersion effect with the comb-like structure of polycarboxylate superplasticizer. At the same time, the hydrophilicity of PEG segments helps to form a hydration film barrier at the pore openings, inhibiting excessive adsorption of superplasticizer by recycled aggregate, thereby prolonging the effective action time of superplasticizer.

[0019] Preferably, the polypropylene glycol shrinkage reducing agent is polypropylene glycol with a molecular weight of 400-1000 Da.

[0020] In this invention, polypropylene glycol is introduced as a shrinkage reducing agent. Its low surface tension characteristics can reduce the surface tension of the liquid phase in the capillary pores of concrete and reduce the negative pressure in the capillary pores, thereby suppressing the capillary shrinkage driving force during the drying process. For recycled aggregate concrete, due to the high porosity inside the aggregate, the risk of drying shrinkage of the hardened paste is more prominent. The addition of PPG-400 can effectively reduce the drying shrinkage rate of concrete without significantly affecting the strength development.

[0021] This invention also protects a method for preparing a slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete as described above, comprising the following steps: Weigh the raw materials according to the formula, add the modifier to deionized water to prepare a solution with a solid content of 20-30%, then add the slow-release polycarboxylate superplasticizer and polypropylene glycol shrinkage reducing agent, stir evenly, and the product is ready.

[0022] In this invention, the preparation method of the slump-retaining and shrinkage-reducing polycarboxylate superplasticizer is simple. It only requires mixing and stirring the modified aqueous solution with the slow-release polycarboxylate superplasticizer mother liquor and polypropylene glycol shrinkage-reducing additive in proportion. No additional high-temperature treatment or special equipment is required. The production operation is convenient and suitable for on-site or factory compounding in engineering applications.

[0023] Compared with the prior art, the present invention has the following beneficial effects: (1) The slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete provided by the present invention adopts a three-component compound system. Through the synergistic effect of slow-release polycarboxylate superplasticizer, modifier and polypropylene glycol shrinkage-reducing additive, it provides a comprehensive solution to the problems of high water absorption, complex pore structure, rapid slump loss and large drying shrinkage of recycled aggregate concrete. It achieves the organic unity of slump retention and shrinkage reduction functions in a single product and avoids the compatibility risk when multiple admixtures are used in combination.

[0024] (2) The slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete provided by the present invention is prepared by using ethylene glycol monovinyl polyethylene glycol ether, acrylic acid, hydroxyethyl acrylate and 2-(phosphoryloxy)ethyl acrylate as raw materials to prepare a quaternary copolymer through free radical copolymerization; wherein, the introduction of the phosphate ester monomer 2-(phosphoryloxy)ethyl acrylate endows the polymer with a strong calcium ion chelating ability, which can form an adsorption layer with a certain stability on the surface of cement particles, slowing down the excessive consumption of the superplasticizer caused by the increase of ion concentration in the pore solution during the hydration process, thereby maintaining the fluidity of the cement paste for a longer period of time and improving the slump retention performance of recycled aggregate concrete.

[0025] (3) The slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete provided by the present invention is prepared by grafting polyethylene glycol segments onto quaternized chitosan modified with gluconic acid. The quaternary ammonium groups impart positive charge to the superplasticizer, enabling it to preferentially accumulate at the negatively charged pores on the surface of the recycled aggregate through electrostatic attraction. The polyhydroxy structure in the gluconic acid segments can undergo hydrogen bonding and coordination interactions with silanol groups and calcium ions on the aggregate surface, further enhancing adsorption stability. The grafted polyethylene glycol segments form a steric barrier at the pores, effectively... It hinders the rapid infiltration of external free water into the pores of the aggregate; the above multiple mechanisms work synergistically, making the modifier more effective at sealing the pores of recycled aggregate than single-function sealing materials, thereby suppressing the adverse effects of aggregate water absorption on the workability of fresh concrete; at the same time, the preparation of the modifier adopts a stepwise grafting route, successively through quaternization, EDC / NHS-mediated amidation coupling and succinic anhydride esterification reaction. The reaction conditions of each step are mild, without the need for high temperature and high pressure or large amounts of organic solvents, and the batch-to-batch repeatability is good, which has a certain basis for industrial scale-up. Detailed Implementation

[0026] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0027] Unless otherwise specified, all chemical reagents and materials in this invention are purchased from the market or synthesized from raw materials purchased from the market.

[0028] Example 1

[0029] A slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete, comprising the following raw materials by weight: 75 parts of slow-release polycarboxylate superplasticizer, 20 parts of modifier, and 8 parts of polypropylene glycol-400.

[0030] The preparation method of the slow-release polycarboxylate superplasticizer is as follows: Add 1500g of ethylene glycol monovinyl polyethylene glycol ether (molecular weight 3000), 110g of acrylic acid, 70g of hydroxyethyl acrylate, and 60g of 2-(phosphoryloxy)ethyl acrylate to 1000g of deionized water. After stirring evenly, a mixed solution is obtained. Add 274g of 7% ammonium persulfate aqueous solution and 192g of 2% vitamin C aqueous solution dropwise over 3.5h. The mixture is then reacted at 25℃ for 1.5h. After the reaction is complete, add NaOH solution to adjust the pH to 6.5, filter, and finally add water until the solid content is 45%.

[0031] The preparation method of the modifier includes the following steps: S1. Add 100g of chitosan to 2.5kg of deionized water, adjust the pH to 10.5, add 70g of 3-chloro-2-hydroxypropyltrimethylammonium chloride, stir at 60℃ for 6h, dialysis to purify after the reaction is complete, freeze dry to obtain quaternized chitosan. S2. Add 100g gluconic acid to 2000g MES buffer (pH 5.5), add 100g EDC and 70g NHS, and activate at 23℃ for 45min to obtain activated gluconic acid solution; add 100g quaternized chitosan to 3000g deionized water, stir and adjust pH to 7.5, then add 1000g gluconic acid solution dropwise, and react at 23℃ for 14h. After the reaction is complete, dialysis purification is performed. The molecular weight cutoff for dialysis is 3500Da, the dialysis time is 48h, and the water is changed every 12h. Freeze-dry to obtain gluconic acid modified chitosan. S3. 100g of polyethylene glycol monomethyl ether (molecular weight 400) and 20g of succinic anhydride were reacted in anhydrous pyridine at 50℃ for 10h. After purification, carboxylated polyethylene glycol was obtained. Then, 100g of carboxylated polyethylene glycol was added to 1500g of PBS buffer (pH 5.5), along with 50g of EDC and 35g of NHS. The mixture was activated at 23℃ for 45min to obtain an activated solution. 100g of gluconate-modified chitosan was added to 2500g of PBS buffer, followed by the addition of 700g of the activated solution. The mixture was amidated at 23℃ for 21h. After the reaction was completed, the mixture was purified by dialysis. The molecular weight cutoff for dialysis was 10000Da, and the dialysis time was 72h. The mixture was then freeze-dried to obtain the modified agent.

[0032] A method for preparing a slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete includes the following steps: Weigh the raw materials according to the formula, add the modifier to deionized water to prepare a solution with a solid content of 25%, then add the slow-release polycarboxylate superplasticizer and polypropylene glycol shrinkage reducing agent, stir evenly, and the product is obtained.

[0033] Example 2

[0034] A slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete, characterized in that it comprises the following raw materials in parts by weight: 70 parts of slow-release polycarboxylate superplasticizer, 15 parts of modifier, and 5 parts of polypropylene glycol-400.

[0035] The preparation method of the slow-release polycarboxylate superplasticizer is as follows: Add 1200g of ethylene glycol monovinyl polyethylene glycol ether (molecular weight 3000), 80g of acrylic acid, 40g of hydroxyethyl acrylate and 30g of 2-(phosphoryloxy)ethyl acrylate to 1000g of deionized water. After stirring evenly, add 282g of 5% ammonium persulfate aqueous solution and 188g of 1% vitamin C aqueous solution dropwise over 4 hours. React at 20℃ for 2 hours. After the reaction is complete, add NaOH solution to adjust the pH to 6, filter, and finally add water until the solid content is 45%.

[0036] The preparation method of the modifier includes the following steps: S1. Add 100g of chitosan to 2kg of deionized water, adjust the pH to 10, add 60g of 3-chloro-2-hydroxypropyltrimethylammonium chloride, stir and react at 55℃ for 7h, after the reaction is completed, dialysis purification, freeze drying to obtain quaternized chitosan. S2. Add 100g gluconic acid to 1500g MES buffer (pH 5.5), add 80g EDC and 50g NHS, and activate at 20℃ for 50min to obtain activated gluconic acid solution; add 100g quaternized chitosan to 2000g deionized water, stir and adjust pH to 7, then add 800g gluconic acid solution dropwise, and react at 20℃ for 16h. After the reaction is complete, dialysis purification is performed. The molecular weight cutoff for dialysis is 3500Da, the dialysis time is 48h, and the water is changed every 12h. Freeze-dry to obtain gluconic acid modified chitosan. S3. 100g of polyethylene glycol monomethyl ether (molecular weight 400) and 15g of succinic anhydride were reacted in anhydrous pyridine at 45°C for 12h. After purification, carboxylated polyethylene glycol was obtained. Then, 100g of carboxylated polyethylene glycol was added to 1000g of PBS buffer (pH 5.5), along with 40g of EDC and 25g of NHS. The mixture was activated at 20°C for 50min to obtain an activated solution. 100g of gluconate-modified chitosan was added to 2000g of PBS buffer, followed by the addition of 500g of the activated solution. The mixture was amidated at 20°C for 24h. After the reaction was completed, the mixture was purified by dialysis. The molecular weight cutoff for dialysis was 10000Da, and the dialysis time was 72h. The mixture was then freeze-dried to obtain the modified agent.

[0037] A method for preparing a slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete includes the following steps: Weigh the raw materials according to the formula, add the modifier to deionized water to prepare a solution with a solid content of 25%, then add the slow-release polycarboxylate superplasticizer and polypropylene glycol shrinkage reducing agent, stir evenly, and the product is obtained.

[0038] Example 3

[0039] A slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete, characterized in that it comprises the following raw materials in parts by weight: 80 parts of slow-release polycarboxylate superplasticizer, 25 parts of modifier, and 10 parts of polypropylene glycol-400.

[0040] The preparation method of the slow-release polycarboxylate superplasticizer is as follows: Add 1800g of ethylene glycol monovinyl polyethylene glycol ether (molecular weight 3000), 140g of acrylic acid, 100g of hydroxyethyl acrylate and 80g of 2-(phosphoryloxy)ethyl acrylate to 1000g of deionized water, stir well to obtain a mixed solution, add 250g of 8% ammonium persulfate aqueous solution and 156g of 3% vitamin C aqueous solution dropwise over 3 hours, and react at 30℃ for 1 hour. After the reaction is complete, add NaOH solution to adjust the pH to 7, filter, and finally add water until the solid content is 45% to obtain the final product.

[0041] The preparation method of the modifier includes the following steps: S1. Add 100g of chitosan to 3kg of deionized water, adjust the pH to 11, then add 80g of 3-chloro-2-hydroxypropyltrimethylammonium chloride, stir and react at 65℃ for 5h, after the reaction is completed, dialysis purification, freeze drying to obtain quaternized chitosan. S2. Add 100g gluconic acid to 2500g MES buffer (pH 6.0), add 120g EDC and 80g NHS, and activate at 25℃ for 40min to obtain activated gluconic acid solution; add 100g quaternized chitosan to 4000g deionized water, stir and adjust pH to 7.5, then add 1200g gluconic acid solution dropwise, and react at 25℃ for 12h. After the reaction is complete, dialysis purification is performed. The molecular weight cutoff for dialysis is 3500Da, the dialysis time is 48h, and the water is changed every 12h. Freeze-dry to obtain gluconic acid modified chitosan. S3. 100g of polyethylene glycol monomethyl ether (molecular weight 400) and 25g of succinic anhydride were reacted in anhydrous pyridine at 55°C for 8h. After purification, carboxylated polyethylene glycol was obtained. Then, 100g of carboxylated polyethylene glycol was added to 2000g of PBS buffer (pH 6.0), along with 60g of EDC and 40g of NHS. The mixture was activated at 25°C for 40min to obtain an activated solution. 100g of gluconate-modified chitosan was added to 3000g of PBS buffer, followed by the addition of 900g of the activated solution. The mixture was amidated at 25°C for 18h. After the reaction was completed, the mixture was purified by dialysis. The molecular weight cutoff for dialysis was 10000Da, and the dialysis time was 72h. The mixture was then freeze-dried to obtain the modified agent.

[0042] A method for preparing a slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete includes the following steps: Weigh the raw materials according to the formula, add the modifier to deionized water to prepare a solution with a solid content of 25%, then add the slow-release polycarboxylate superplasticizer and polypropylene glycol shrinkage reducing agent, stir evenly, and the product is obtained.

[0043] Comparative Example 1 A slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete, comprising the following raw materials by weight: 75 parts of slow-release polycarboxylate superplasticizer and 8 parts of polypropylene glycol-400.

[0044] The preparation method of the slow-release polycarboxylate superplasticizer is as follows: Add 1500g of ethylene glycol monovinyl polyethylene glycol ether (molecular weight 3000), 110g of acrylic acid, 70g of hydroxyethyl acrylate, and 60g of 2-(phosphoryloxy)ethyl acrylate to 1000g of deionized water. After stirring evenly, a mixed solution is obtained. Add 274g of 7% ammonium persulfate aqueous solution and 192g of 2% vitamin C aqueous solution dropwise over 3.5h. The mixture is then reacted at 25℃ for 1.5h. After the reaction is complete, add NaOH solution to adjust the pH to 6.5, filter, and finally add water until the solid content is 45%.

[0045] A method for preparing a slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete includes the following steps: Weigh the raw materials according to the formula, and mix the slow-release polycarboxylate superplasticizer and polypropylene glycol shrinkage reducing agent evenly to obtain the final product.

[0046] Compared with Example 1, the slump-retaining and shrinkage-reducing polycarboxylate superplasticizer in this comparative example did not contain any modifier.

[0047] Comparative Example 2 A slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete, comprising the following raw materials by weight: 75 parts of slow-release polycarboxylate superplasticizer, 20 parts of modifier, and 8 parts of polypropylene glycol-400.

[0048] The preparation method of the slow-release polycarboxylate superplasticizer is as follows: Add 1500g of ethylene glycol monovinyl polyethylene glycol ether (molecular weight 3000), 110g of acrylic acid, 70g of hydroxyethyl acrylate, and 60g of 2-(phosphoryloxy)ethyl acrylate to 1000g of deionized water. After stirring evenly, a mixed solution is obtained. Add 274g of 7% ammonium persulfate aqueous solution and 192g of 2% vitamin C aqueous solution dropwise over 3.5h. The mixture is then reacted at 25℃ for 1.5h. After the reaction is complete, add NaOH solution to adjust the pH to 6.5, filter, and finally add water until the solid content is 45%.

[0049] The preparation method of the modifier includes the following steps: 100g of chitosan was added to 2.5kg of deionized water, the pH was adjusted to 10.5, and then 70g of 3-chloro-2-hydroxypropyltrimethylammonium chloride was added. The mixture was stirred at 60℃ for 6 hours. After the reaction was completed, the mixture was purified by dialysis and freeze-dried to obtain the modifier.

[0050] A method for preparing a slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete includes the following steps: Weigh the raw materials according to the formula, add the modifier to deionized water to prepare a solution with a solid content of 25%, then add the slow-release polycarboxylate superplasticizer and polypropylene glycol shrinkage reducing agent, stir evenly, and the product is obtained.

[0051] Compared to Example 1, the modifier in this comparative example was replaced with quaternized chitosan.

[0052] Comparative Example 3 A slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete, comprising the following raw materials by weight: 75 parts of slow-release polycarboxylate superplasticizer, 20 parts of modifier, and 8 parts of polypropylene glycol-400.

[0053] The preparation method of the slow-release polycarboxylate superplasticizer is as follows: Add 1500g of ethylene glycol monovinyl polyethylene glycol ether (molecular weight 3000), 110g of acrylic acid, 70g of hydroxyethyl acrylate, and 60g of 2-(phosphoryloxy)ethyl acrylate to 1000g of deionized water. After stirring evenly, a mixed solution is obtained. Add 274g of 7% ammonium persulfate aqueous solution and 192g of 2% vitamin C aqueous solution dropwise over 3.5h. The mixture is then reacted at 25℃ for 1.5h. After the reaction is complete, add NaOH solution to adjust the pH to 6.5, filter, and finally add water until the solid content is 45%.

[0054] The preparation method of the modifier includes the following steps: 100g of chitosan was added to 2.5kg of deionized water, the pH was adjusted to 10.5, and then 70g of 3-chloro-2-hydroxypropyltrimethylammonium chloride was added. The mixture was stirred at 60℃ for 6h. After the reaction was completed, the mixture was purified by dialysis and freeze-dried to obtain quaternized chitosan. S2. Add 100g gluconic acid to 2000g MES buffer (pH 5.5), add 100g EDC and 70g NHS, and activate at 23℃ for 45min to obtain activated gluconic acid solution; add 100g quaternized chitosan to 3000g deionized water, stir and adjust pH to 7.5, then add 1000g gluconic acid solution dropwise, and react at 23℃ for 14h. After the reaction is complete, dialysis purification is performed. The molecular weight cutoff for dialysis is 3500Da, the dialysis time is 48h, and the water is changed every 12h. Freeze-dry to obtain the modifier.

[0055] A method for preparing a slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete includes the following steps: Weigh the raw materials according to the formula, add the modifier to deionized water to prepare a solution with a solid content of 25%, then add the slow-release polycarboxylate superplasticizer and polypropylene glycol shrinkage reducing agent, stir evenly, and the product is obtained.

[0056] Compared to Example 1, the modifier in this comparative example was replaced with gluconic acid-modified chitosan.

[0057] Comparative Example 4 A slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete, comprising the following raw materials by weight: 75 parts of slow-release polycarboxylate superplasticizer, 20 parts of modifier, and 8 parts of polypropylene glycol-400.

[0058] The preparation method of the slow-release polycarboxylate superplasticizer is as follows: Add 1500g of ethylene glycol monovinyl polyethylene glycol ether (molecular weight 3000), 110g of acrylic acid, and 70g of hydroxyethyl acrylate to 1000g of deionized water. After stirring evenly, a mixed solution is obtained. Add 268g of 7% ammonium persulfate aqueous solution and 188g of 2% vitamin C aqueous solution dropwise over 3.5h. The mixture is then reacted at a constant temperature of 25℃ for 1.5h. After the reaction is complete, add NaOH solution to adjust the pH to 6.5, filter, and finally add water until the solid content is 45%.

[0059] The preparation method of the modifier includes the following steps: S1. Add 100g of chitosan to 2.5kg of deionized water, adjust the pH to 10.5, add 70g of 3-chloro-2-hydroxypropyltrimethylammonium chloride, stir at 60℃ for 6h, dialysis to purify after the reaction is complete, freeze dry to obtain quaternized chitosan. S2. Add 100g gluconic acid to 2000g MES buffer (pH 5.5), add 100g EDC and 70g NHS, and activate at 23℃ for 45min to obtain activated gluconic acid solution; add 100g quaternized chitosan to 3000g deionized water, stir and adjust pH to 7.5, then add 1000g gluconic acid solution dropwise, and react at 23℃ for 14h. After the reaction is complete, dialysis purification is performed. The molecular weight cutoff for dialysis is 3500Da, the dialysis time is 48h, and the water is changed every 12h. Freeze-dry to obtain gluconic acid modified chitosan. S3. 100g of polyethylene glycol monomethyl ether (molecular weight 400) and 20g of succinic anhydride were reacted in anhydrous pyridine at 50℃ for 10h. After purification, carboxylated polyethylene glycol was obtained. Then, 100g of carboxylated polyethylene glycol was added to 1500g of PBS buffer (pH 5.5), along with 50g of EDC and 35g of NHS. The mixture was activated at 23℃ for 45min to obtain an activated solution. 100g of gluconate-modified chitosan was added to 2500g of PBS buffer, followed by the addition of 700g of the activated solution. The mixture was amidated at 23℃ for 21h. After the reaction was completed, the mixture was purified by dialysis. The molecular weight cutoff for dialysis was 10000Da, and the dialysis time was 72h. The mixture was then freeze-dried to obtain the modified agent.

[0060] A method for preparing a slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete includes the following steps: Weigh the raw materials according to the formula, add the modifier to deionized water to prepare a solution with a solid content of 25%, then add the slow-release polycarboxylate superplasticizer and polypropylene glycol shrinkage reducing agent, stir evenly, and the product is obtained.

[0061] Compared to Example 1, the slow-release polycarboxylate superplasticizer in this comparative example did not introduce 2-(phosphoryloxy)ethyl acrylate.

[0062] The slump-retaining and shrinkage-reducing polycarboxylate superplasticizers prepared in Examples 1-3 and Comparative Examples 1-4 were used in recycled aggregate concrete for performance testing. The recycled aggregates were selected according to GB / T 25177-2010 "Recycled Coarse Aggregates for Concrete," specifically Class II recycled coarse aggregates with a particle size of 5-31.5 mm. The main technical specifications were as follows: fine powder content ≤2.0%, mud lump content ≤0.5%, and apparent density ≥2450 kg / m³. 3Water absorption ≤5.0%, crushing index ≤15%, needle-like and flaky particle content ≤10%; reference concrete mix proportion: cement (P·O 42.5) 350 kg / m³ 3 1050 kg / m³ of recycled aggregate 3 Natural fine aggregate (river sand, fineness modulus 2.6-2.8) 720 kg / m³ 3 Water 157.5 kg / m 3 The water-cement ratio is 0.45, and the amount of admixture (based on solid content) is 0.2% of the amount of cementitious material. Concrete slump and time-related loss were tested according to GB / T 50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures". Concrete was mixed according to the mix proportion, and after adding admixtures, it was mixed for 90 s, and the initial slump was measured immediately. The mixture was then placed in an environment of (20±2)℃, and the slump was measured again after 60 min and 120 min, followed by re-mixing for 30 s. The retention rate (%) of the relative initial slump at each time point was calculated. Three samples were prepared in parallel for each group, and the average value was taken. Compressive strength was tested according to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". 150 mm × 150 mm × 150 mm cube specimens were formed and cured to the specified age (28 d). A uniaxial compression test was conducted using a compression testing machine at a loading rate of (0.5±0.1) MPa / s. The average value of the three specimens was taken as the representative strength value for that group. Drying shrinkage was tested according to GB / T The test was conducted according to GB / T 50082-2009 "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete" (Shrinkage Test Section). A 100 mm × 100 mm × 515 mm prism specimen was formed and cured under standard conditions (temperature 20±2℃, relative humidity ≥95%) for 24 hours. The specimen was then demolded, and the initial length was measured using a contact extensometer. Subsequently, the specimens were placed in a constant temperature and humidity chamber at (20±2)℃ and (60±5)% relative humidity. The length was measured again after 28 days, and the drying shrinkage rate was calculated. Three specimens were prepared for each group, and the average value was taken. The 28-day electrical flux test was conducted according to GB / T 50082-2009 (using the electrical flux method). A cylindrical specimen with a diameter of 100 mm and a height of 50 mm was formed and cured under standard conditions for 28 days. After pretreatment with a vacuum saturation device, a 60 V DC voltage was applied to both ends for 6 consecutive days. h, record the cumulative electrical flux (C) through the specimen. Prepare 3 specimens for each group and take the average value; the test results are shown in Table 1 below.

[0063] Table 1

[0064] As can be seen from Table 1 above, the performance of Examples 1-3 is better than that of the comparative examples. The initial slump, slump retention rate at 60 min and 120 min are all better, and the 28-day compressive strength, 28-day drying shrinkage rate and 28-day electrical flux performance are good. This shows that the slump-retaining and shrinkage-reducing polycarboxylate superplasticizer provided by the present invention has excellent workability retention, mechanical properties and durability. In comparison, Comparative Example 1 (without modifier) ​​had the worst slump retention and drying shrinkage, indicating that the modifier significantly contributes to both slump retention and shrinkage reduction. Comparative Examples 2 and 3 replaced the complete modifier with intermediate products, and their performance was between that of Comparative Example 1 and the examples. Moreover, they gradually improved with the increase of the integrity of the modifier structure, verifying the sequential increase in the performance of the modifier by gluconic acid grafting and PEG grafting. Comparative Example 4 lacked phosphate monomers, and its slump retention performance decreased significantly while its shrinkage reduction effect was less affected, proving that the introduction of 2-(phosphoryloxy)ethyl acrylate has an irreplaceable role in the anchoring and adsorption of slow-release polycarboxylate superplasticizer in recycled aggregate concrete systems.

[0065] The above description is a further detailed explanation of the present invention in conjunction with specific implementation examples. It should not be considered that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, several simple deductions or substitutions can be made without departing from the concept of the present invention, and all such deductions or substitutions should be considered to fall within the protection scope of the present invention.

[0066] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete, characterized in that, By weight, it includes the following ingredients: 70-80 parts of slow-release polycarboxylate superplasticizer, 15-25 parts of modifier, and 5-10 parts of polypropylene glycol shrinkage reducing agent.

2. The slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete according to claim 1, characterized in that, By weight, it includes the following raw materials: 75-80 parts of slow-release polycarboxylate superplasticizer, 20-25 parts of modifier, and 7-10 parts of polypropylene glycol shrinkage reducing agent.

3. The slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete according to claim 1, characterized in that, The preparation method of the slow-release polycarboxylate superplasticizer is as follows: Add ethylene glycol monovinyl polyethylene glycol ether, acrylic acid, hydroxyethyl acrylate and 2-(phosphoryloxy)ethyl acrylate to deionized water, stir until homogeneous to obtain a mixed solution, add ammonium persulfate aqueous solution and vitamin C aqueous solution dropwise, carry out a constant temperature reaction, add NaOH solution after the reaction is completed, adjust the pH, filter, and finally add water to the preset solid content to obtain the final product.

4. The slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete according to claim 3, characterized in that, The molecular weight of the ethylene glycol monovinyl polyethylene glycol ether is 2000-3000 Da; the mass ratio of the deionized water, ethylene glycol monovinyl polyethylene glycol ether, acrylic acid, hydroxyethyl acrylate, and 2-(phosphoryloxy)ethyl acrylate is 100:120-180:8-14:4-10:3-8; the mass fraction of the ammonium persulfate aqueous solution is 5-8%, and the amount used is 8-12% of the mass of the mixed solution; the mass fraction of the vitamin C aqueous solution is 1-3%, and the amount used is 5-8% of the mass of the mixed solution; the constant temperature reaction temperature is 20-30℃, and the time is 1-2 hours; the pH is 6-7, and the preset solid content is 40-50%.

5. The slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete according to claim 1, characterized in that, The preparation method of the modifier includes the following steps: S1. Disperse chitosan powder in deionized water, adjust the pH to 10-11, add 3-chloro-2-hydroxypropyltrimethylammonium chloride, stir and react, dialyze to purify after the reaction is complete, freeze dry to obtain quaternized chitosan; S2. Add gluconic acid to MES buffer, add EDC and NHS for activation to obtain activated gluconic acid solution; add quaternized chitosan to deionized water, stir and adjust pH to 7-7.5, then add gluconic acid solution dropwise, carry out constant temperature reaction, after the reaction is completed, dialysis purification, freeze drying to obtain gluconic acid modified chitosan. S3. Polyethylene glycol monomethyl ether was reacted with succinic anhydride in anhydrous pyridine and purified to obtain carboxylated polyethylene glycol. Then, it was added to PBS buffer, and EDC and NHS were added for activation to obtain an activated solution. Gluconic acid-modified chitosan was added to PBS buffer, followed by the addition of the activated solution to carry out an amidation reaction. After the reaction was completed, it was purified by dialysis and freeze-dried to obtain the modifier.

6. The slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete according to claim 5, characterized in that, In step S1, the mass ratio of chitosan, deionized water, and 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1:20-30:0.6-0.8, and the stirring reaction temperature is 55-65℃ for 5-7 hours.

7. The slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete according to claim 5, characterized in that, In step S2, the mass ratio of gluconic acid, MES buffer, EDC, and NHS is 1:15-25:0.8-1.2:0.5-0.8, the activation temperature is 20-25℃, and the time is 40-50 min; the mass ratio of quaternized chitosan, deionized water, and gluconic acid solution is 1:20-40:8-12, the isothermal reaction temperature is 20-25℃, and the time is 12-16 h; the molecular weight cutoff for dialysis is 3500 Da, the dialysis time is 48 h, and the water is changed every 12 h.

8. The slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete according to claim 5, characterized in that, In step S3, the molecular weight of the polyethylene glycol monomethyl ether is 400-1000 Da, the mass ratio of polyethylene glycol monomethyl ether to succinic anhydride is 1:0.15-0.25, the reaction temperature is 45-55℃, and the time is 8-12 h; the mass ratio of the carboxylated polyethylene glycol, PBS buffer, EDC, and NHS is 1:10-20:0.4-0.6:0.25-0.4, the activation temperature is 20-25℃, and the time is 40-50 min; the mass ratio of the gluconate-modified chitosan, PBS buffer, and activation solution is 1:20-30:5-9, the amidation reaction temperature is 20-25℃, and the time is 18-24 h; the molecular weight cutoff for dialysis is 10000 Da, and the dialysis time is 72 h.

9. The slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete according to claim 1, characterized in that, The polypropylene glycol shrinkage reducing agent is polypropylene glycol with a molecular weight of 400-1000 Da.

10. A method for preparing a slump-retaining and shrinkage-reducing polycarboxylate superplasticizer for recycled aggregate concrete as described in any one of claims 1-9, characterized in that, Includes the following steps: Weigh the raw materials according to the formula, add the modifier to deionized water to prepare a solution with a solid content of 20-30%, then add the slow-release polycarboxylate superplasticizer and polypropylene glycol shrinkage reducing agent, stir evenly, and the product is ready.